Diversified quality production revisited the transformation of production systems and regulatory regimes in Germany - Arndt Sorge; Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2016)
We revisit the concept of Diversified Quality Production (DQP), which we introduced about thirty years ago. Our purpose is to examine the extent to which the concept can still be considered tenable for describing and explaining the development of the interaction between the political economy and concepts of production, notably in Germany. First, we show why and in which ways DQP was more heterogeneous than we had originally understood. Then, on the basis of evidence with respect to political, business, and economic changes in Germany, we show that DQP Mark I, a regime by and large characteristic of the 1980s, turned into DQP Mark II. In the process, major "complementarities" disappeared between the late 1980s and now - mainly the complementarity between production modes on the one hand and industrial relations and economic regulation on the other. While the latter exhibit greater change, business strategies and production organization show more continuity, which helps explain how Germany maintained economic performance after the mid-2000s, more than other countries in Europe. Conceptually, our most important result is that the complementarities emphasized in political economy are historically relative and limited, so that they should not be postulated as stable configurations. – – Dies ist eine Neubetrachtung des Konzepts der Differenzierten Qualitätsproduktion (DQP), das vor etwa dreißig Jahren von uns eingeführt wurde. Wir prüfen, inwieweit das Konzept noch zur Beschreibung und Erklärung der Wechselwirkung zwischen politischer Ökonomie und Produktionskonzepten taugt, vor allem in Deutschland. Zuerst zeigen wir, dass DQP vielgestaltiger war, als wir uns dies zunächst vorgestellt hatten. Danach diskutieren wir vor dem Hintergrund des politischen sowie betriebs- und volkswirtschaftlichen Wandels in Deutschland, wie DQP Mark I, ein vor allem in den 1980er-Jahren vorherrschendes Regime, zu DQP Mark II wurde. Dabei verschwanden zentrale "Komplementaritäten", insbesondere die zwischen Produktionsweisen einerseits und Arbeitsbeziehungen und wirtschaftlicher Regulierung andererseits. Während die letzteren mehr Veränderung aufwiesen, zeigten Geschäftsstrategien und Produktionsorganisation mehr Kontinuität. Dadurch erklärt sich die im Vergleich zu anderen europäischen Ländern stabile deutsche Wirtschaftsleistung nach 2005. In konzeptioneller Hinsicht ist unser wichtigstes Ergebnis, dass die in der politischen Ökonomie betonten Komplementaritäten historisch relativ und zeitlich begrenzt sind; sie sollten deshalb nicht als stabile Konfigurationen vorausgesetzt werden.
Keywords: 300; production concepts; manufacturing; diversified quality production; industrial organization; industrial relations; industrial restructuring; globalization; skills; Germany; Produktionskonzepte; industrielle Fertigung; diversifizierte Qualitätsproduktion; Industrieökonomik; Arbeitsbeziehungen; Strukturwandel; Globalisierung; Qualifikationen; Deutschland